Straight and Curved Conformations of FtsZ Are Regulated by GTP Hydrolysis - Lu, Chunlin (American Society for Microbiology, 2000)
FtsZ assembles in vitro into protofilaments that can adopt two conformations—the straight conformation, which can assemble further into two-dimensional protofilament sheets, and the curved conformation, which forms minirings about 23 nm in diameter. Here, we describe the structure of FtsZ tubes, which are a variation of the curved conformation. In the tube the curved protofilament forms a shallow helix with a diameter of 23 nm and a pitch of 18 or 24°. We suggest that this shallow helix is the relaxed structure of the curved protofilament in solution. We provide evidence that GTP favors the straight conformation while GDP favors the curved conformation. In particular, exclusively straight protofilaments and protofilament sheets are assembled in GMPCPP, a nonhydrolyzable GTP analog, or in GTP following chelation of Mg, which blocks GTP hydrolysis. Assembly in GDP produces exclusively tubes. The transition from straight protofilaments to the curved conformation may provide a mechanism whereby the energy of GTP hydrolysis is used to generate force for the constriction of the FtsZ ring in cell division.